The Development of a Game Application for Enhancing Systematic Thinking Skills in Grade 5 Students - Chaichana, Thanyaporn; Petchsangroj, Thanwarat; Supaluk, Sutiwat; Srikeaw, Daruwan (Reading Journal, 2025)
This study aims to: (1) develop a game application to enhance systematic thinking skills among Grade 5 students, (2) evaluate the quality of the game application, (3) examine students’ systematic thinking abilities after playing the game, and (4) assess students' satisfaction with the application. The research instruments included: (1) the game application designed for systematic thinking development, (2) an evaluation form assessing the content and media quality of the game, (3) a systematic thinking ability test for Grade 5 students, and (4) a satisfaction questionnaire regarding the application. The sample group consisted of 36 Grade 5 students from Na Luang School, Bangkok, selected through simple random sampling by drawing lots for one classroom. The findings revealed that: (1) the game application demonstrated a high level of quality, with media quality rated as very good ( = 4.59, S.D. = 0.44) and content quality rated as good ( = 4.33, S.D. = 0.56) (2) students’ systematic thinking abilities exceeded the 70% performance benchmark; and (3) students’ satisfaction with the game application was at the highest level ( = 4.51, S.D.= 0.75) These results suggest that the developed game application is effective and suitable for practical use in enhancing systematic thinking skills among Grade 5 students.